STRATEGI PENGEMBANGAN EKOWISATA SEBAGAI UPAYA PENINGKATAN PENDAPATAN PELAKU UMKM DI WISATA HUTAN BAMBU MATADOR, BEKASI - Noviandari Sari Utami; Muhammad Sholeh; Rangga Dalu Aji Toana; Muhammad Daffa Andiara (JURNAL LENTERA BISNIS, 2024)
In 2021, Jatirangga Village was designated as one of 125 creative villages assisted by the Ministry of Tourism and Creative Economy of the Republic of Indonesia (Kemenparekraf RI). The newest concept, Jatirangga Village plans to develop tourism potential in the area, one of which is the matador bamboo forest. The aim of this research is to identify, analyze and formulate an ecotourism development strategy that can increase the income of MSMEs in the Matador Bekasi bamboo forest tourism. The research method was carried out using a qualitative descriptive approach. Data collection was carried out by triangulation, observation, documentation and interviews with tourist attraction managers, MSMEs and tourists. The presence of the Matador Bamboo Forest tourist attraction increases income for MSMEs, although it has not significantly improved the community's economy because the number of visitors is not large. Promotional facilities are lacking and strategies for developing the Matador Bamboo Forest tourist attraction have not been running optimally, which has had an impact on the number of visitors who come. Suggestions that researchers can give for future development include: Tourist attraction managers increasing promotion through social media, local government communities, tourist attraction managers carrying out environmental arrangements and revitalizing facilities and infrastructure to increase interest in visiting Matador bamboo forest tourism, tourist attraction managers and MSMEs receive training and assistance so that the existence of the Matador bamboo forest ecotourism has a significant impact on improving the economy for the surrounding community. Key words: Strategy, Bamboo Forest Ecotourism, MSMEs, Increasing Income